Level Pengelolaan Keuangan Berbasis Literasi Keuangan Dan Inklusi Keuangan Pada Pasar Cidu Kuliner Kota Makassar - Hairul Amri; Muhammad Nur Abdi; Nurul Fuada (Pusat Riset dan Inovasi Nasional, 2025)
This research is a quantitative study aimed at determining the level of financial management influenced by financial literacy and financial inclusion among traders at the Cidu Culinary Market in Makassar City. A total sample of 66 traders was selected randomly using the Slovin formula. Primary data was obtained through questionnaires arranged using a Likert scale. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 25. The results showed that financial literacy and financial inclusion simultaneously have a positive and significant effect on the financial management of traders. These findings emphasize the importance of enhancing education and access to financial services to improve financial management and support the sustainability of traditional market traders' businesses.